The Use of Peer Teaching in Student Team Achievement Division to Improve Narrative Writing Achievement - Dahlin, Yulinda Aulia; Sinaga, Tuntun; Sukirlan, Muhammad (Universitas PGRI Sumatera Barat, 2025)
This study investigates the efficacy of incorporating peer teaching in Student Teams-Achievement Divisions (STAD) to enhance students' writing achievement in narrative text. Recognizing the challenges faced by EFL students in organizing ideas and the limitations inherent in traditional pedagogical approaches, this research examines whether the integration of peer teaching in STAD group activities can improve the quality and structure of students' written work. A comparative analysis was conducted between students who were taught using peer teaching in STAD and those who received instruction through the original STAD. The objective of the study is to assess whether significant differences in writing achievement exist between the two groups, with a particular focus on content, organization, vocabulary, language use, and mechanical accuracy. The results indicate a substantial improvement in students' writing skills, suggesting that the incorporation of peer teaching in STAD can serve as an effective pedagogical strategy for enhancing writing proficiency in the EFL context, especially in the domain of narrative text production.